Governance of Blockchain and Distributed Ledger Technology Projects - Bronwyn E. Howell; Petrus H. Potgieter; Bert M. Sadowski (International Telecommunications Society (ITS), 2019)
Blockchains are the most well-known example of a distributed ledger technology (DLT). Unlike classic databases, the ledger is not maintained by any central authority. The integrity of the ledger is maintained automatically by an algorithmic consensus process whereby nodes vote and agree upon the authoritative version. In effect, the consensus algorithm operates in the manner of a decision-making process within a governance system. The technological characteristics of blockchain systems are well documented (Narayanan, Bonneau, Felton and Miller, 2016). We propose that one of the reasons why it has so far proved very difficult to seed large-scale commercial DLT (blockchain) projects lies in the arena of project ownership and governance. Unlike classic centralised database systems, DLTs have no one central point of "ownership" of any of the system's infrastructure or data. In this piece of exploratory research, we propose applying theories of club governance to both the technical design and operational development of a range of DLT (blockchain) systems, including (but not necessarily limited to) cryptocurrencies and enterprise applications to explore how they can explain the development of (or lack of development of) sustainable solutions to real business problems. There are many parallels to the governance arrangements observed historically in the origins of complex distributed telecommunications networks.
Keywords: 330; blockchain; distributed ledger; governance; club governance; distributed consensus